Angiography and Endovascular Therapy for Peripheral Artery Disease - Yokoi, Yoshiaki; Fukuda, Keisuke; Fujihara, Masahiko; Higashimori, Akihiro; Kawarada, Osami (IntechOpen, 2017)
This textbook on Angiography and Endovascular Therapy for Peripheral Artery Disease provides a comprehensive angiographic approach to assess and determine optimal treatment strategies for peripheral artery disease (PAD). Each chapter focuses on angiography as it relates to the outcomes of endovascular work. It is an overview of the results obtained from a large number of actual cases with over 100 angiographic images of aortoiliac, femoropopliteal, below-the-knee, and below-the-ankle artery disease. Diagnostic and angiographic images of nonatherosclerotic PAD are also included. Anyone who is engaged in or preparing to engage in endovascular work for PAD should find this book useful as a reference and as an instruction material.